Association Between Cardiovascular Health Status and Healthcare Utilization in a Large Integrated Healthcare System - Irvin Lien, MD; Howard Moffet, MPH; Jennifer Liu, MPH; Andrew Karter, PhD; Matthew Solomon, MD, PhD; Alan Go, MD; Khurram Nasir, MD, MPH; Stephen Sidney, MD, MPH; Jamal Rana, MD, PhD (Elsevier, 2024)
Introduction: The American Heart Association Life's Simple 7 schema can be used to categorize patients' cardiovascular health status as poor, intermediate, or ideal on the basis of smoking, BMI, physical activity, dietary patterns, blood pressure, cholesterol, and fasting blood sugar. This study examined the association between cardiovascular health status and subsequent healthcare utilization. Methods: This was an observational cohort study of adults from an integrated healthcare delivery system-Kaiser Permanente Northern California-that had outpatient care between 2013 and 2014. Patients were categorized by American Heart Association cardiovascular health status: poor, intermediate, or ideal. Individual-level healthcare utilization and costs in 2015 were accumulated for each patient and compared across the 3 cardiovascular health categories and stratified by age groups. Results: A total of 991,698 patients were included in the study. A total of 194,003 (19.6%) were aged 18-39 years; 554,129 (55.9%) were aged 40-64 years; and 243,566 (24.6%) were aged ≥65 years. A total of 259,931 (26.2%) had ideal cardiovascular health; 521,580 (52.6%) had intermediate cardiovascular health; and 210,187 (21.2%) had poor cardiovascular health. Healthcare utilization measured by average relative cost per patient increased monotonically across age categories (p<0.001). In addition, cardiovascular health category was inversely associated with lower cost in each age group (p<0.001). Conclusions: Adults who were younger and had more ideal cardiovascular health had relatively lower healthcare costs across age groups. Interventions to promote better cardiovascular health may improve patient outcomes and reduce overall healthcare expenditures.